2020
DOI: 10.1002/per.2281
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and behavioural responses to Coronavirus disease 2019: The role of personality

Abstract: This study examined the associations between personality traits and psychological and behavioural responses to the coronavirus disease 2019 (COVID‐19) pandemic. Personality was assessed in January/February 2020 when the public was not aware of the spread of coronavirus in the USA. Participants were reassessed in late March 2020 with four sets of questions about the pandemic: concerns, precautions, preparatory behaviours, and duration estimates. The sample consisted of N = 2066 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

55
266
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(354 citation statements)
references
References 71 publications
55
266
12
1
Order By: Relevance
“…Emotionally unstable individuals also have more dysfunctional interpersonal relationships and are less satisfied with their relationships (Vater and Schröder-Abé 2015). Among the five factors of personality, neuroticism has been demonstrated to be the strongest correlate for reduced well-being and enhanced loneliness (Albuquerque et al 2012;Buecker et al 2020), which has also been confirmed in recent Covid-19-related studies (Aschwanden et al 2020;Modersitzki et al 2020).…”
Section: Introductionmentioning
confidence: 69%
“…Emotionally unstable individuals also have more dysfunctional interpersonal relationships and are less satisfied with their relationships (Vater and Schröder-Abé 2015). Among the five factors of personality, neuroticism has been demonstrated to be the strongest correlate for reduced well-being and enhanced loneliness (Albuquerque et al 2012;Buecker et al 2020), which has also been confirmed in recent Covid-19-related studies (Aschwanden et al 2020;Modersitzki et al 2020).…”
Section: Introductionmentioning
confidence: 69%
“…This research adds to a growing body of work on how personality and individual differences predict compliance with health guidelines and other attitudes and behaviors during the pandemic (e.g., Aschwanden et al, 2020 ; Blagov, 2020 ; Nowak et al, 2020 ; Zajenkowski et al, 2020 ). 5 We studied entitlement in this paper because past research had identified a link between entitlement and ignoring instructions ( Zitek & Jordan, 2019 ), and because people have been quick to label those who are not following the guidelines as “entitled” (e.g., Weekman, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…All individual compliance items were significantly correlated with entitlement except mask wearing (see Appendix B ). Other personality research has also revealed a different pattern of results for mask wearing as compared to other pandemic health guidelines ( Aschwanden et al, 2020 ; Shook et al, 2020 ).…”
Section: Studymentioning
confidence: 97%
“…There is now also an emerging literature on the relationship between personality and people's response to the COVID 19 pandemic. Researchers have examined personality correlates of a wide range of variables including pathogen avoidance (Makhanova & Shepherd, 2020), economic anxiety (Mann, Krueger, & Vohs, 2020), compliance with government advice (De Coninck et al, 2020;Zajenkowski et al, 2020), safety behaviors (Aschwanden et al, 2020;Blagov, 2020;Carvalho, Pianowski, & Gonçalves, 2020), consumer stockpiling (Dammeyer, 2020;Garbe, Rau, & Toppe, 2020), and concerns about coronavirus (Bacon & Corr, 2020). There have also been several studies correlating personality with well-being during various phases of the COVID-19 pandemic (e.g., Jørgensen, Bor, Lindholt, & Petersen, 2020;Kroencke, Geukes, Utesch, Kuper, & Back, 2020;Michinov & Michinov, 2020;Modersitzki, Phan, Kuper, & Rauthmann, 2020;Qian & Yahara, 2020;Russo, Hanel, Altnickel, & van Berkel, 2020;Zajenkowski et al, 2020).…”
Section: Personality and Well-being Under Covidmentioning
confidence: 99%
“…Despite an emerging literature on the effect of the COVID-19 pandemic on well-being (for reviews, see Sher, 2020;Xiong et al, 2020) and the effect of personality on people's response to the pandemic (e.g., Aschwanden et al, 2020;Bacon & Corr, 2020;Blagov, 2020;De Coninck, d'Haenens, & Matthijs, 2020;Krasavtseva, Kiseleva, Kasyan, & Pushkar, 2020;Peters et al, 2020;Zajenkowski, Jonason, Leniarska, & Kozakiewicz, 2020), many gaps in understanding remain. First, most studies examining the effect of COVID-19 on well-being are cross-sectional surveys conducted during the pandemic that lack a meaningful Pre-COVID comparison group.…”
mentioning
confidence: 99%